2021
DOI: 10.1021/acs.iecr.1c04080
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Additive-Induced Deactivation of the Cu–ZnO(Al2O3)-Catalyzed γ-Butyrolactone Hydrogenolysis: A Rare Deactivation Process

Abstract: This work reports initial results on the effect of low concentrations (ppm level) of a stabilizing agent (2,6-di- tert -butyl-4-methylphenol, BHT) present in an off-the-shelf solvent on the catalyst performance for the hydrogenolysis of γ-butyrolactone over Cu–ZnO-based catalysts. Tetrahydrofuran (THF) was employed as an alternative solvent in the hydrogenolysis of γ-butyrolactone. It was found that the Cu–ZnO catalyst performance using a reference solvent (1,4-dioxane) was good, meaning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…of 933.1 eV (marked in blue in Fig. 5B) is assigned to Cu 0 /Cu þ species, while the component at about 934.6 eV (red) corresponds to Cu 2þ species [87,88]. The additional peak at about a 936.1 eV (dark yellow) can be ascribed to copper hydroxide (Cu(OH) 2 ) [89,90].…”
Section: Characterization Of Materialsmentioning
confidence: 97%
“…of 933.1 eV (marked in blue in Fig. 5B) is assigned to Cu 0 /Cu þ species, while the component at about 934.6 eV (red) corresponds to Cu 2þ species [87,88]. The additional peak at about a 936.1 eV (dark yellow) can be ascribed to copper hydroxide (Cu(OH) 2 ) [89,90].…”
Section: Characterization Of Materialsmentioning
confidence: 97%
“…In the Cu−ZnO catalyzed γ-butyrolactone hydrogenation system, the ppm level of a stabilizing agent (2,6-di-tert-butyl-4-methylphenol, BHT) in solvent THF could poison the interfacial Cu−ZnO sites, leading to the deactivation of Cu−ZnO-catalyzed γ-butyrolactone hydrogenation. 151 Although Cu-based catalysts showed high efficiency in the hydrogenation of γ-valerolactone or γ-butyrolactone, Huber et al found the reaction rate of γ-butyrolactone hydrogenation to 1,4-butanediol upon Co/TiO 2 -R is >8 times more active than Cu/TiO 2 -R. 152 Introducing 5−25 mol % of Cu to the Co/TiO 2 -R could further increase the production rate of 1,4-butanediol by 2.1−2.5 times. The formation of a CuCo alloy with a Co-rich core and Cu-rich shell is responsible for the high reaction rate and 1,4-butanediol selectivity.…”
Section: Synergistic Catalysis Of Metallic and Brønsted Acid Sitesmentioning
confidence: 99%
“…In addition, the introduction of LaO x suppresses the oxidation of Cu during the reaction, ensuring the catalyst stability during multiple recycles. In the Cu–ZnO catalyzed γ-butyrolactone hydrogenation system, the ppm level of a stabilizing agent (2,6-di- tert -butyl-4-methylphenol, BHT) in solvent THF could poison the interfacial Cu–ZnO sites, leading to the deactivation of Cu–ZnO-catalyzed γ-butyrolactone hydrogenation …”
Section: Heterogeneous Synergistic Catalysts Of Ring-opening Hydrogen...mentioning
confidence: 99%